Extraction of phenolic compounds: A review - Alara, Oluwaseun Ruth; Nour, A. H.; Ukaegbu, Chinonso Ishmael (Elsevier B.V., 2021)
Phenolic compounds are parts of secondary metabolites mostly found in plant species with enormous structural diversities. They can exist as glycosides or aglycones; matrix or free-bound compounds; and comprising mostly polymerized or monomer structures. Additionally, these compounds are not universally dispensed within plants with varied stability. This has contributed to challenging extraction processes; implying that employing a single step or inappropriate extraction technique might change the recovery of phenolic components from the plant samples. Hence, it is important to select an appropriate extraction method so as to recover the targeted phenolic compounds. This is will helps to recover substantial yields from the sample matrix. Therefore, this review mainly focuses on the phenolic compounds and several methods of extraction that are used to obtaining them from plant materials. These extraction methods includes both conventional and unconventional techniques.